Uncovering Factors Influencing Interpersonal Health Communication - Lennie Donné; Carel Jansen; John Hoeks (SAGE Publishing, 2017)
Talking to friends, family, or peers about health issues might, among other things, increase knowledge of social norms and feelings of self-efficacy in adopting a healthier lifestyle. We often see interpersonal health communication as an important mediating factor in the effects of health campaigns on health behavior. No research has been done so far, however, on factors that influence whether and how people talk about health issues without being exposed to a health campaign first. In this exploratory study, we interviewed 12 participants about their communication behavior concerning six different health themes, like smoking and exercising. The results suggest that at least four types of interpersonal health communication can be distinguished, each influenced by different factors, like conversational partner and objective of the conversation. Future research should take this diversity of interpersonal health communication into account, and focus on designing health campaigns that aim to trigger dialogue within target populations.